2012
DOI: 10.3389/fimmu.2012.00158
|View full text |Cite
|
Sign up to set email alerts
|

Gene Conversion-Like Events in the Diversification of Human Rearranged IGHV3-23*01 Gene Sequences

Abstract: Gene conversion (GCV), a mechanism mediated by activation-induced cytidine deaminase (AID) is well established as a mechanism of immunoglobulin diversification in a few species. However, definitive evidence of GCV-like events in human immunoglobulin genes is scarce. The lack of evidence of GCV in human rearranged immunoglobulin gene sequences is puzzling given the presence of highly similar germline donors and the presence of all the enzymatic machinery required for GCV. In this study, we undertook a computati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 129 publications
(171 reference statements)
0
11
1
Order By: Relevance
“…Immunoglobulin gene conversion (GC) events are common in some organisms, such as rabbit [18] and chicken [18], while there is some evidence that it rarely occurs in human [8,9]. Despite the fact that studies have analyzed GC events from limited sequencing data, there does not exist a tool for identifying gene conversio in immunoglobulin sequences.…”
Section: Gene Conversion Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunoglobulin gene conversion (GC) events are common in some organisms, such as rabbit [18] and chicken [18], while there is some evidence that it rarely occurs in human [8,9]. Despite the fact that studies have analyzed GC events from limited sequencing data, there does not exist a tool for identifying gene conversio in immunoglobulin sequences.…”
Section: Gene Conversion Identificationmentioning
confidence: 99%
“…Lavinder et al, 2014 [18] approach analyzing GC using a variation of the GENECONV permutation test. Duvvuri et al, 2012 [9] use two approaches: GENECONV [23] and visual assessment.…”
Section: Gene Conversion Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al [14] have used mfg for analyses of transcription-associated mutations, and suggest that the genome sequence has evolved to increase protein evolvability under stress. In mfg analyses of human rearranged IGHV3-2301 gene sequences Duvvuri et al [20] found that hypermutable bases were located in the ssDNA of stable SLSs.…”
Section: How To Use Our Computer Algorithm Mfgmentioning
confidence: 99%
“…However, models are only valid and useful if they have demonstrated predictive value. Kinetic models created by our computer program, mfg , have frequently demonstrated predictive value in the analyses of mutagenesis in three very different systems: Escherichia coli [1115], the p53 tumor suppressor gene [10, 16], and in somatic hypermutation (SHM) during the immune response [1720]. In these analyses, mutation frequencies were determined experimentally during transcription and during mfg -simulated transcription in order to predict: (1) the location of mutable bases in loops of high-stability secondary structures, and (2) the effects of transcription, supercoiling, and secondary structure stabilities on base mutability.…”
Section: Introductionmentioning
confidence: 99%